Efficacy Of Herbal Formulation As Amalakyavaleha In Pandu W.S.R To Anemia In Children - Upadhyay, Aditya Narayan; Gupta, M N; Verma, Mithilesh (International Research Journal of Ayurveda & Yoga, 2020)
Anemia is a common micronutrients disease affect health status of very large population of whole world. Iron deficiency is most common cause of anemia. Ayurveda described Pandu Roga which correlate with anemia. Ayurveda mentioned as causes, symptoms and treatment of Pandu. Pandu Roga involves lack of hemoglobin due to poor intake of iron through dietary sources. Poor absorption and digestive problems may also lead anemia. The characteristic feature of diseases involve discoloration of skin, pita and presence of Ketaki dhuli nibh chaya. Ayurveda described it as “Varnoplakshita roga” which indicates change in colour. The clinical symptoms involve loss of appetite, palpitation, Pandutwa and fatigue. In the classification the disease Pandu felt in the group of Varna in which there are significant changes in the normal color of the body. The detail description of Pandu Roga its classification starts from Ayurvedic Samhitas only. Pandu Roga is one of the diseases mentioned in Ayurveda characterized by whitish discoloration of skin due to loss of blood. The disease is comparable with anemia in the modern medical literature. The incidence of problem is high in school going children, adolescent and pregnant women.The main nutrients involved in the synthesis of hemoglobin are iron, folic acid and Vitamin B12 . In public health terms, iron deficiency is by far the first cause of nutritional anemia worldwide. Folic acid deficiency is less widespread and is often observed with iron deficiency anemia. Vitamin B12 deficiency is far rare. Therefore, the focus in this article is on Iron-deficiency anemia in children.